PENINGKATAN HASIL PEMBELAJARAN LOMPAT JAUH MELALUI PENDEKATAN BERMAIN LONGU PADA SISWA KELAS IV SDN 145 BINONGJATI - Sutiawan, Asep (Globalwriting Academica Consulting & Publishing, 2022)
The purpose of this study was to improve the long jump learning outcomes through the longu playing approach to the fourth-grade students of SDN 145 Binongjati. This study uses a classroom action research method using 2 cycles with the research subjects being class IV students, totaling 31 students. The research instruments used in this study were observation and questionnaires. The data analysis of this research used quantitative and qualitative descriptive. The results of this study indicate that through the approach of playing kangaroo jump on the long jump material using aqua bottle and pralon media as learning facilities and infrastructure can improve the learning outcomes of fourth grade students at SD Negeri 145 Binongjati. The suggestions submitted based on the results of this study are expected for elementary school physical education teachers to use Classroom Action Research (CAR) in learning, teachers can vary various forms of games in learning, and aqua bottles and pralon media can be used to overcome the shortage of teaching aids in learning. long jump.